Pemanfaatan Sempadan Pantai Kedonganan oleh Pengusaha Cafe Berdasarkan Perda Kabupaten Badung Nomor 26 Tahun 2013 - I Gede Yogi Arya Windiarta; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2021)
Spatial plans that are accommodated in a legal norm both at the central, provincial and city levels are in synergy with each other. The purpose of this study is to find out the legal arrangements in the Badung RTRW Regional Regulation on the use of the Kedonganan beach border by cafe entrepreneurs and what sanctions are imposed on the cafe entrepreneurs if they violate the Badung RTRW Regional Regulation. To achieve this goal, a normative research method is used using a statutory approach and a conceptual approach. The results of the study, namely the regulation of cafe entrepreneurs who set up cafes on the Kedonganan beach border, are regulated in Article 74 paragraph (2) letter d of the Badung Regency Regulation Number 26 of 2013 that by not building permanently on the beach border. In addition, it must also pay attention to the public interest. Sanctions that can be imposed on cafe entrepreneurs who set up cafes on the Kedonganan beach border if they violate the Badung Regency Regulation Number 26 of 2013 include criminal sanctions, namely Article 115 in the form of imprisonment or fines. Administrative sanctions in the form of written warnings; temporary suspension of activities: temporary suspension of public services; business closure; license revocation; license cancellation; demolition of buildings; restoration of space functions; and/or administrative fines as regulated in Article 112 paragraph (2).